Early Emergence of Agreement in Yucatec Maya Sign Language - Olivier Le Guen (Languages, 2022)
In many sign languages, space is used to express grammatical features. However, verb agreement in space is noticeably slow to appear in emerging sign languages. Many reasons have been proposed to explain this delay or even absence: the reduced size of the community, the recent creation of the sign language and the lack of exposure to a fully formed language. To examine the way space is used to express agreement in Yucatec Maya Sign Language (YMSL), a new signed language from the peninsula of Yucatán (Mexico), a task was conducted using video stimuli created to elicit ditransitive constructions showing transfer events, such as events of giving or taking. Results show that agreement is present early in YMSL, even from the first generation of deaf signers. While many signers used single agreement constructions, the second generation of deaf children systematically employed double agreement constructions, placing them on the high end of the evolutionary path proposed for verb agreement in sign languages. I argue that cultural habits of the surrounding community, namely the preference for a geocentric frame of reference among Yucatec Maya speakers, is what facilitates the early emergence of the use of space to express agreement in YMSL.